Differential infection outcome of Chlamydia trachomatis in human blood monocytes and monocyte-derived dendritic cells - Datta, Baishakhi (BMC Microbiol, 2014)
BACKGROUND: Chlamydia trachomatis is an intracellular bacteria which consist of three biovariants; trachoma (serovars A-C), urogenital (serovars D-K) and lymphogranuloma venereum (L1-L3), causing a wide spectrum of disease in humans. Monocytes are considered to disseminate this pathogen throughout the body while dendritic cells (DCs) play an important role in mediating immune response against bacterial infection. To determine the fate of C. trachomatis within human peripheral blood monocytes and monocyte-derived DCs, these two sets of immune cells were infected with serovars Ba, D and L2, representative of the three biovariants of C. trachomatis. RESULTS: Our study revealed that the different serovars primarily infect monocytes and DCs in a comparable fashion, however undergo differential infection outcome, serovar L2 being the only candidate to inflict active infection. Moreover, the C. trachomatis serovars Ba and D become persistent in monocytes while the serovars predominantly suffer degradation within DCs. Effects of persistence gene Indoleamine 2, 3-dioxygenase (IDO) was not clearly evident in the differential infection outcome. The heightened levels of inflammatory cytokines secreted by the chlamydial infection in DCs compared to monocytes seemed to be instrumental for this consequence. The immune genes induced in monocytes and DCs against chlamydial infection involves a different set of Toll-like receptors, indicating that distinct intracellular signalling pathways are adopted for immune response. CONCLUSION: Our results demonstrate that the host pathogen interaction in chlamydia infection is not only serovar specific but manifests cell specific features, inducing separate immune response cascade in monocytes and DCs.